Optimal sizing and techno-enviro-economic feasibility assessment of solar tracker-based hybrid energy systems for rural electrification in Sudan. (March 2023) - Ahmed, Eihab E.E.; Demirci, Alpaslan; Tercan, Said Mirza
Abstract: Hybrid power systems (HPS) based on photovoltaic (PV), diesel generators (DG), and energy storage systems (ESS) are widely used solutions for the energy supply of off-grid or isolated areas. The main hybridizing challenges are reliability, investment and operating costs, and carbon emissions problems. Since HPS are usually sized to provide energy continuously, it is essential to use the solar energy potential close to full capacity, especially on cloudy days. One of the prominent solutions to overcome these challenges is integrating solar tracking systems (STS). This article focuses on the optimal sizing of HPS based on PV-DG-ESS utilizing STS by analyzing technical, economic, and environmental aspects. Optimization is performed with the MILP solved via Gurobi, considering the net present cost (NPC) and loss of power supply probability (LPSP) objectives. The results indicate that horizontal and dual solar trackers can provide up to 50% better energy harvest performance and reduce NPC by up to 7%. It is also found that there is no significant difference in cost reduction between both systems. Moreover, STS is feasible if the cost is less than 375 USD and 250 USD for Sudan and South Sudan, respectively.